2007
DOI: 10.1111/j.1875-595x.2007.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries prevalence and risk factors among 12-year old schoolchildren from Baghdad, Iraq: a post-war survey

Abstract: It is important to maintain the low prevalence of caries among children by increasing awareness and promoting oral health care strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
40
5
23

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 17 publications
13
40
5
23
Order By: Relevance
“…La méconnaissance des parents sur l'importance de la santé bucco-dentaire était la raison la plus fréquemment citée (P ≤ 0,05). La source de l'éducation bucco-dentaire était le facteur indépendant le plus souvent associé aux caries dentaires sévères (OR = 2,35 ; IC à 95 % : 1,80-2,60) ; la fréquence de l'utilisation du fil dentaire était le facteur prédictif le plus important corrélé à une gingivite (OR = 3,51 ; IC : 1,44). …”
unclassified
See 1 more Smart Citation
“…La méconnaissance des parents sur l'importance de la santé bucco-dentaire était la raison la plus fréquemment citée (P ≤ 0,05). La source de l'éducation bucco-dentaire était le facteur indépendant le plus souvent associé aux caries dentaires sévères (OR = 2,35 ; IC à 95 % : 1,80-2,60) ; la fréquence de l'utilisation du fil dentaire était le facteur prédictif le plus important corrélé à une gingivite (OR = 3,51 ; IC : 1,44). …”
unclassified
“…Despite the declining rate of caries occurrence in developed countries [2], surveys still suggest a high prevalence of this disease in Middle-Eastern children [3,4]. Studies carried out in this region have shown the rate of caries experience ranging from 62% to 74.8% for schoolchildren [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Modern evidence revealed that there is a continuum of disease states ranging from sub-clinical subsurface changes to more advanced, clinical detectable subsurface caries (called "intact" surface layers) to various stages of more advance lesions with microscopic and later macroscopic cavitations of enamel and significant involvement of dentine (Ahmed et al, 2007). Reisine and Poster (2001) believe that the risk factors for dental caries include physical and biological factors (e.g., a high number of cariogenic bacteria and immunological components) and behavioral factors (poor oral hygiene, poor dietary habits, frequent use of oral medication containing sugars, insufficient exposure to fluoride and inadequate use of dental-health-care services).…”
Section: Introductionmentioning
confidence: 99%
“…Namal ve ark., 6-12 yaş grubu çocuklarda yaptığı çalışmada, annelerin eğitim düzeyinin çocukların çürük diş sayısını etkilemediği belirtmiştir (29). Anne tahsili ile diş çürüğü arasında ilişki olduğunu belirten çalışmalar olduğu gibi aksini söyleyen çalışmalarda vardır (30)(31)(32)(33).…”
Section: Discussionunclassified